Characteristics of Cases with Poor Transcranial Motor-evoked Potentials Baseline Waveform Derivation in Spine Surgery: A Prospective Multicenter Study of the Monitoring Committee of the Japanese Society for Spine Surgery and Related Research. Issue 22 (15th November 2021) - Kobayashi, Kazuyoshi; Imagama, Shiro; Ando, Kei; Yoshida, Go; Ando, Muneharu; Kawabata, Shigenori; Yamada, Kei; Kanchiku, Tsukasa; Fujiwara, Yasushi; Taniguchi, Shinichirou; Iwasaki, Hiroshi; Shigematsu, Hideki; et al.
Abstract : Study Design: Prospective multicenter study. Objective: The purpose of the study is to examine cases with poor baseline waveform derivation for all muscles in multichannel monitoring of transcranial motor-evoked potentials (Tc-MEPs) in spine surgery. Summary of Background Data: Intraoperative neuromonitoring (IONM) is useful for identifying neurologic deterioration during spinal surgery. Tc-MEPs are widely used for IONM, but some cases have poor waveform derivation, even in multichannel Tc-MEP monitoring. Methods: The subjects were 3625 patients (mean age 60.1 years, range 4–95; 1886 females, 1739 males) who underwent Tc-MEP monitoring during spinal surgery at 16 spine centers between April 2017 and March 2020. Baseline Tc-MEPs were recorded from the deltoid, abductor pollicis brevis, adductor longus, quadriceps femoris, hamstrings, tibialis anterior, gastrocnemius, and abductor hallucis (AH) muscles after surgical exposure of the spine. Results: The 3625 cases included cervical, thoracic, and lumbar lesions (50%, 33% and 17%, respectively) and had preoperative motor status of no motor deficit, and motor deficit with manual muscle testing (MMT) ≥3 and MMT <3 (70%, 24% and 6%, respectively). High-risk surgery was performed in 1540 cases (43%). There were 73 cases with poor baseline waveform derivation (2%), and this was significantly associated with higher body weight, body mass index, thoracic lesions, motor deficit of MMT <3, high-risk surgery (42/1540 [2.7%] vs. 31/2085 [1.5%], P  < 0.05), and surgery for ossification of the posterior longitudinal ligament (OPLL). Intraoperative waveform derivation occurred in 25 poor derivation cases (34%) and the AH had the highest rate. Conclusion: The rate of poor baseline waveform derivation in spine surgery was 2% in our series. This was significantly more likely in high-risk surgery for thoracic lesions and OPLL, and in cases with preoperative severe motor deficit. In such cases, it may be preferable to use multiple modalities for IONM to derive multichannel waveforms from distal limb muscles, including the AH. Level of Evidence: 3 Abstract : In a prospective multicenter study, 73 cases (2%) had poor baseline waveform derivation of transcranial motor-evoked potentials (Tc-MEPs) in 3625 patients who underwent spinal surgery at 16 spine centers. Poor baseline waveform derivation was significantly associated with thoracic lesions, motor deficit of manual muscle testing <3, high-risk surgery, and surgery for ossification of the posterior longitudinal ligament.